COVID-19 Vaccine Acceptance in a Sample From the United Arab Emirates General Adult Population: A Cross-Sectional Survey, 2020 - Albahri, Abdulaziz Hussain; Alnaqbi, Shahad Ahmed; Alshaali, Asma Obaid; Alnaqbi, Shatha Ahmed; Shahdoor, Shaikha Mohammad (Frontiers in Public Health, 2021)
Introduction: The COVID-19 pandemic has placed a tremendous stress on economies and healthcare systems worldwide. Having a vaccine is one of the promising solutions. However, vaccination hesitancy is becoming a recognized future challenge. This study aims to evaluate the current vaccine hesitancy in a segment of the United Arab Emirates (UAE) general public and its associated factors. Methods: This was an online cross-sectional survey that took place from the 14th to the 19th of September 2020 across the UAE. The questionnaire asked the participants about their willingness to receive the COVID-19 vaccine in the future. Multivariable logistic regression analysis was used to assess the association between vaccination willingness and the participants' sociodemographic factors, experiences and beliefs regarding COVID-19, and previous influenza vaccine uptake. Results: There was a total of 2,705 participants; 72.5% were females, and 69.8% were Emirati nationals. A total of 1,627 (60.1%) participants were willing to take the COVID-19 vaccine in the future. There were statistically significant associations between the following factors and vaccine acceptance: male gender, non-Emiratis, younger age group, residents of Sharjah and the Northern Emirates, having lesser educational attainment, perceived increased personal or public risk of contracting the disease [aOR = 1.71, 95% CI (1.35–2.17), p < 0.0001; aOR = 1.84, 95% CI (1.44–2.36), p < 0.0001, respectively], and increased perception of serious outcome from the disease. Conversely, vaccine hesitancy was associated with unemployment, not receiving the influenza vaccine within the past 2 years [aOR = 0.36, 95% CI (0.30–0.44), p < 0.0001], not believing in the seriousness of the COVID-19 situation or the vaccine's ability to control the pandemic, and not believing that the public authorities are handling the pandemic adequately. Having contracted the disease or knowing someone who has did not show a statistically significant association with vaccine acceptance. Vaccine safety, side effects, and the belief that one needs to develop immunity naturally were the top reasons for vaccination hesitancy. Conclusion: Given the level of vaccine hesitancy in the study population, this needs to be evaluated in a more representative sample of the whole population. If confirmed, this would signify the need for coordinated local and international initiatives to combat vaccine misinformation and reassure the public regarding vaccine safety and efficacy.